Geomorphological, Electrical Resistivity and Magnetic Methods for Assessing Groundwater Potential in Adet Town, West Gojam, Ethiopia - Belay Sitotaw Goshu; Kirubel Molla (Britain International of Exact Sciences (BIoEx) Journal, 2026)
Imagine the sun-scorched fields of Adet Town, West Gojam, and Ethiopia, where families rise each day with a flicker of hope, their hands calloused from carrying water across cracked earth. This study, "Geomorphological, Electrical Resistivity and Magnetic Methods for Assessing Groundwater Potential," breathes life into their dreams, weaving a heartfelt narrative through science to uncover hidden aquifers beneath volcanic plains. Guided by the Amhara National Regional State Water Irrigation and Energy Office Bureau (ANRSWIEOB), we walked the land, 50-meter traverses marking our steps, mapping magnetic fields that dance from 33,900 to 37,400 nT, resistivity layers hinting at low-conductivity zones, and geomorphic contours revealing a 644-meter eastward drop shaped by ancient floods. The findings are a beacon of resilience: magnetic anomalies, like those at PpW3 and Shena, signal fractured basalt where water might pool, with variability (σ up to 3,120 nT) reflecting tectonic gifts and challenges, dry wells a stark lesson from Tali Spring. Resistivity profiles illuminate perched aquifers, while Nile-like escarpments guide us to faulted recharge paths, echoing Adet’s rugged terrain. Statistically, slopes (-1.1 nT/m) and ranges (3,500 nT in BH BRIG) highlight deep structures, promising yields yet demanding care to avoid depletion, as seen in Lake Tana’s decline. Humanly, it’s a story of community, elders sharing spring lore, children dreaming of wells, scientists blending past wisdom with modern tools. The results reveal hope amid scarcity, urging sustainable stewardship. The land speaks, and we listen, turning geophysical whispers into flowing lifelines for Adet’s people, a testament to humanity’s enduring bond with the earth.